Pengaruh Rasio Keuangan dan Ukuran Perusahaan terhadap Return Saham Jakarta Islamic Index 70 - Ilham Ramadhan Ersyafdi; Zakiyah Aslamiyah (Fakultas Ekonomi, UIN Maliki Malang, 2023)
Sharia-based investments are increasingly in demand by investors. An example of this phenomenon is the emergence of a new Islamic stock index, namely the Jakarta Islamic Index (JII) 70. One of the aims of investors is to expect a good rate of return on what they have invested. This study aims to analyze whether JII 70 stock returns can be influenced by financial ratios and company size variables with objects namely companies that have been listed on the index from 2018-2020. The population in this study was 101 companies through purposive sampling, 21 companies were used as samples. There are nine variables used in this study with the results showing that stock returns can be influenced by three variables, namely debt to equity ratio, price earning ratio, dividend per share. Meanwhile, stock returns cannot be influenced by six other independent variables including return on assets, earnings per share, economic value added, total asset turnover, net profit margin and company size.